INDONESIA’S DEFENSE DIPLOMACY THROUGH HUMANITARIAN ASSISTANCE TO FIJI - Anak Agung Banyu Perwita; Muhammad Arkan; Yasintha Selly Rossiana; Annisa Dipa Pertiwi (Universitas Jenderal Ahmad Yani, 2022)
Natural disasters tend to be vulnerable to attack the Fiji Islands as a Pacific country which is geographically composed of large and small islands. On the other hand, this condition also occurs in Indonesia, which is also an archipelago country that is prone to natural disasters. Seeing the shared conditions experienced by Fiji, Indonesia often provides humanitarian assistance to Fiji when it is hit by natural disasters. This research explores disaster diplomacy, in which we will analyze diplomatic efforts in a state relationship, through disaster-based assistance between Indonesia and Fiji. Further disaster diplomacy can be defined as how and why disaster-related activities can or cannot cause the emergence of cooperation between parties or can reduce the occurrence of conflict. The purpose of this study is to analyze how Indonesia's defense diplomacy with Fiji is through disaster relief. The results of this study explain how disaster relief can be a means of Indonesia's defense diplomacy to provide a positive image and gain support in Pacific countries. This can be seen from Fiji who wants to expand cooperation by signing an MoU on defense with Indonesia after the assistance provided by Indonesia in 2017. After the establishment of this cooperation in the defense sector, a positive attitude was also shown by Fiji by providing support to Indonesia at the Melanesian Spearhead Group (MSG) meeting. In this study, the method used is literature review by collecting credible data from various sources such as journals, website articles, news, and even official documents from the government.